Extending the radius of family-centered care in the pediatric cardiac intensive care unit through virtual rounding. Issue 1 (18th January 2022) - Tallent, Sarah; Turi, Jennifer L.; Thompson, Julie; Allareddy, Veerajalandhar; Hueckel, Rémi
ABSTRACT: Background: The arrival of COVID-19 brought urgent limitation of visitation in hospitals across the country. Family-centered care and its delivery rapidly changed and left the family behind—unable to actively participate in their loved one's care. Local problem: A southeastern academic medical center pediatric cardiac intensive care unit (PCICU) needed to augment family-centered medical rounds when parents could not be at the bedside. No alternative to physical presence for daily medical rounds existed in the PCICU. Methods: A virtual rounding (VR) program was implemented allowing parents of patients admitted to PCICU to join medical rounds remotely through teleconferencing. Preintervention and postintervention rounding times, staff perceptions of the program, and parental satisfaction scores using the Pediatric Family Satisfaction in the Intensive Care Unit (pFS-ICU) tool were measured. Interventions: This quality improvement project implemented a VR program offered to all families of patients in the PCICU. Results: VR did not increase rounding times after implementation ( p = .673). Staff satisfaction surveys revealed that staff felt the VR program did not prolong rounding times ( p ≤ 0.001), workload impact perceptions improved after intervention ( p = <0.001), and staff felt VR should be offered to families in PCICU ( p ≤ 0.001). Only nine pFS-ICU surveys were completed giving the family a limited voice in the evaluation of this project. Conclusions: This project demonstrates that VR can be successfully implemented for family engagement without increased burden on staff.